The benefit of the pan-Romance perspective: A new attempt to solve the tecedor/tecedeira puzzle. (March 2019) - Rainer, Franz
Abstract : In Old Spanish and in Portuguese the name of a female agent is sometimes expressed with a suffix that coincides with one of the suffixes used in these languages in the formation of instrument nouns, as in Portuguese tecedor 'weaver' vs. tecedeira 'female weaver'. The etymology of this female suffix has long been a puzzle for Hispanists and Lusitanists. Although it has been known since Meyer-Lübke that there are parallels in other Romance varieties, the problem has never been tackled from a pan-Romance perspective in a systematic way. The purpose of the present paper is to do just that. It is argued that these suffixes denoting female agents arose as a consequence of the ellipsis of the head noun in Latin noun phrases containing a noun referring to a female and an adjective in - toria . The alternative of viewing the modern suffixes as the result of the coalescence of the Latin agentive suffix - tor and the female suffix - ia of words like avia 'granny' is also explored.